From Oral Traditional to Digital: The Role of Technology in Preserving Javanese Cultural Heritage - Nunik Mila Sari; M Hasbullah Ridwan (RETORIKA: Jurnal Ilmu Bahasa, 2025)
The transition to the digital age presents challenges and opportunities for cultural heritage preservation. This research analyzes the role of technology in preserving Javanese cultural heritage through an in-depth study of the video of the song “Saleho” popularized by Denny Caknan and Abah Lala on the YouTube platform. The research uses a descriptive qualitative approach. Data were collected from visual observation, lyric analysis, and field notes, focusing on the coding and interpretation of visual and textual meanings, through videos uploaded on the two singers’ official YouTube channels. The analysis used semiotic theory, to identify the denotative and connotative meanings of Javanese cultural values contained in the songs and visualizations presented. The results show that Denny Caknan and Abah Lala have successfully utilized digital platforms to introduce the song “Saleho” to a wider audience, including the younger generation. The use of traditional Javanese costumes and lyrics that are rich in meaning are effective strategies in popularizing the song. However, this study also found modern adaptations in the song’s presentation aimed at attracting listeners, indicating the potential influence of cultural representations on young audience perceptions and cross-cultural adaptation. Implications include the development of a digital cultural heritage preservation methodology and policy recommendations for the creative industries.  Digital technology, especially the YouTube platform, has an important role in the preservation of Javanese songs. Through the case analysis of the song “Saleho”, this research contributes to a deeper understanding of how traditional music can be adapted into a digital format without losing its cultural essence.